Harnessing Treg Homeostasis to Optimize Posttransplant Immunity: Current Concepts and Future Perspectives - Ikegawa, Shuntaro; Matsuoka, Ken-ichi (Frontiers in Immunology, 2021)
CD4+CD25+Foxp3+ regulatory T cells (Tregs) are functionally distinct subsets of mature T cells with broad suppressive activity and have been shown to play an important role in the establishment of immune tolerance after allogeneic hematopoietic stem cell transplantation (HSCT). Tregs exhibit an activated phenotype from the stage of emigration from the thymus and maintain continuous proliferation in the periphery. The distinctive feature in homeostasis enables Tregs to respond sensitively to small environmental changes and exert necessary and sufficient immune suppression; however, on the other hand, it also predisposes Tregs to be susceptible to apoptosis in the inflammatory condition post-transplant. Our studies have attempted to define the intrinsic and extrinsic factors affecting Treg homeostasis from the acute to chronic phases after allogeneic HSCT. We have found that altered cytokine environment in the prolonged post-HSCT lymphopenia or peri-transplant use of immune checkpoint inhibitors could hamper Treg reconstitution, leading to refractory graft-versus-host disease. Using murine models and clinical trials, we have also demonstrated that proper intervention with low-dose interleukin-2 or post-transplant cyclophosphamide could restore Treg homeostasis and further amplify the suppressive function after HSCT. The purpose of this review is to reconsider the distinctive characteristics of post-transplant Treg homeostasis and discuss how to harness Treg homeostasis to optimize posttransplant immunity for developing a safe and efficient therapeutic strategy.